2022
DOI: 10.3390/en15228546
|View full text |Cite
|
Sign up to set email alerts
|

Superheated Steam Spray Drying as an Energy-Saving Drying Technique: A Review

Abstract: Drying is an extremely energy-intensive process. Superheated steam as a drying medium can improve the energy efficiency of the drying processes. In superheated steam drying, waste heat can be recovered by condensing the exhaust steam or raising its specific enthalpy. Spray drying is widely used in industry, even though its energy efficiency is often low. Substitution of air by superheated steam as a drying medium in a spray dryer may reduce the energy consumption of the drying process by 20–30%; moreover, if e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 56 publications
(91 reference statements)
0
3
0
Order By: Relevance
“…Energies 2024, 17, 3051 7 of 50 organic matter is subject to the steps illustrated in Figure 7 [33] and further described in Table 1. The analysis of this process has drawn a lot of research to improve historical procedures [34][35][36] in which all steps and energy provided were considered individually. Uçal et al [37] analyzed a whole milk powder (WMP) production line principally based on natural gas for heating purposes and showed that pasteurization, evaporation, and drying represented 98.3% of the energy consumption and 95.7% of the CO2 emissions-for a total of 10.2 MJ/kgWMP and 0.588 kgCO2/kgWMP.…”
Section: Dairy Application: Sterilized Milk Powdermentioning
confidence: 99%
See 1 more Smart Citation
“…Energies 2024, 17, 3051 7 of 50 organic matter is subject to the steps illustrated in Figure 7 [33] and further described in Table 1. The analysis of this process has drawn a lot of research to improve historical procedures [34][35][36] in which all steps and energy provided were considered individually. Uçal et al [37] analyzed a whole milk powder (WMP) production line principally based on natural gas for heating purposes and showed that pasteurization, evaporation, and drying represented 98.3% of the energy consumption and 95.7% of the CO2 emissions-for a total of 10.2 MJ/kgWMP and 0.588 kgCO2/kgWMP.…”
Section: Dairy Application: Sterilized Milk Powdermentioning
confidence: 99%
“…From the energy utility point of view, high-temperature heat pumps and solar thermal technologies present great potential. Solar thermal implementation has been studied by Camci [35] and Sobulska et al [36], showing that the production of superheated steam with solar collectors leads to energy efficiency gains of 75% and 70% on the drying process, and Shah [39], showing a reduction of 60% of conventional boiler duties with solar thermal collectors' integration at the process level in a dairy plant in Dubai. Regarding heat pumps, Bühler et al [40] showed a potential energy savings of 65% for central heat pump systems and 56% for decentralized heat pumping systems, with a carbon emissions reduction impact of around 80% in the frame of Denmark's electricity mix.…”
Section: Dairy Application: Sterilized Milk Powdermentioning
confidence: 99%
“…10,[13][14][15] Spray drying granulation usually has the problems of complex equipment, a large floor space, a low thermal efficiency and high energy consumption. 20,21 Studies have shown that drying processes, including spray drying, account for about 10-25% of energy consumption in the industrial sector in developed countries and are a significant contributor to the production of greenhouse gases. 22,23 As a typical spherical crystallization process, quasi-emulsion solvent diffusion requires compli-cated and large amounts of multi-solvent systems (such as biohazardous solvents like dichloromethane, tetrachloromethane, and methylbenzene) to satisfy the demanding diffusion relationship between the continuous and dispersed phases.…”
Section: Introductionmentioning
confidence: 99%